Pengembangan E-Module Bercirikan Etnomatematika pada Materi Bangun Ruang Sisi Datar - Kurniasari, Intan; Rakhmawati, Rosida; Fakhri, Jamal (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstract: This research is included in research and development that aims to produce e-module characterized by ethnomathematics on the matter of building a flat side space. Making this e-module using exe-learnig applications. This research use 4-D development model that is Define, Design, Development and Disseminate. The results obtained from the list of experts with an average score of 3,88 and media experts with an average score of 3,90 so that the product has met the eligibility criteria, while the teacher response to get an average score of 3,08 with interesting criteria and response learnes with an average score of 3,52 are included in very interesting criteria. So it can be concluded that the developed e-modue declared eligible for use. Abstrak: Penelitian ini termasuk dalam penelitian dan pengembangan yang bertujuan untuk menghasilkan e-module yang bercirikan etnomatematika pada materi bangun ruang sisi datar. Pembuatan E-module ini menggunakan aplikasi exe-learning. Penelitian ini menggunakan model pengembangan 4-D yaitu Define, Design, Development dan Disseminate. Hasil penelitian yang diperoleh dari penilaian ahli materi dengan skor rata-rata 3,88 dan ahli media dengan skor rata-rata 3,90 sehingga produk dinyatakan telah memenuhi kriteria kelayakan, sedangkan untuk respon pendidik mendapatkan skor rata-rata 3,08 dengan kriteria menarik dan respon peserta didik dengan skor rata-rata 3,52 termasuk dalam kriteria sangat menarik. Sehingga dapat disimpulkan bahwa e-module yang dikembangkan dinyatakan layak untuk digunakan.